Effects of normalizing process and nitriding process on the microstructure, texture, and magnetic properties in low-temperature grain-oriented silicon steel - LI Xia; YANG Ping; JIA Zhi-wei; ZHANG Hai-li (工程科学学报, 2019)
The influences of the normalization parameters and nitriding parameters on the microstructure of normalized samples, the primary recrystallization microstructure, and inhibitors were analyzed by electron backscatter diffraction (EBSD) and scanning electron microscopy (SEM) techniques. The effects of normalizing cooling rates, nitriding temperatures and nitrogen content on the primary recrystallization and secondary recrystallization microstructure, textures, and properties were studied. The results show that grain sizes decrease with the increasing normalizing cooling rate; when the rate is slow, the grain size of high-temperature nitriding sample increases with the slow normalizing cooling rate, reducing the driving force for secondary recrystallization and increasing secondary recrystallization temperature. The acquired inhibitor is insufficient, which leads to unsuccessful secondary recrystallization. High-temperature nitriding and low-temperature nitriding lead to different sizes of inhibitors in the decarburized sheets; however, inhibitors in the surface and subsurface regions of high-temperature nitriding samples are primarily of the same size, while the inhibitors in the surface region of low-temperature nitriding samples are larger than those of the subsurface inhibitors. The lower-temperature nitriding sample with low nitrogen content exhibits a poor magnetic property. As the grain size remains small at a low normalizing temperature and high normalizing cooling rate, the second recrystallization starts at a slightly lower temperature and Brass-type oriented grains are present. The secondary recrystallization of high-temperature nitriding and low-temperature nitriding samples with high nitrogen content could be basically completed; however, the magnetic properties of samples are different, and more grains with deviated {210} < 001> orientation lead to a reduction in magnetic properties.